Oh Gay! al Bagaglino: Uno spettacolo omosessuale di nome, ma non di fatto - Meroni, Andrea (Mimesis Journal, 2021)
In 1979 the Italian theatrical production offered plenty of plays centred upon gay themes, whilst television had already been displaying various characters – mostly from the music scene – whose gender identity and sexual orientation were not seen by the public as “traditional”. In the same year, the fifteen-year-old company “Bagaglino”, run by Mario Castellacci and Pier Francesco Pingitore, abandoned the genre of cabaret and started a new course putting on stage a musical comedy called Oh Gay!, trying to take advantage of the huge success of the Italian-French film La cage aux folles. The comedy is about a gay couple involved in the imaginary kidnapping of the Pope and it combines satire about the gloomy situation of Rome in the Years of Lead with a bland mockery of the multiplication of LGBT people in Italy.